2015
DOI: 10.1039/c5ib00040h
|View full text |Cite
|
Sign up to set email alerts
|

Human breast cancer invasion and aggression correlates with ECM stiffening and immune cell infiltration

Abstract: Tumors are stiff and data suggest that the extracellular matrix stiffening that correlates with experimental mammary malignancy drives tumor invasion and metastasis. Nevertheless, the relationship between tissue and extracellular matrix stiffness and human breast cancer progression and aggression remains unclear. We undertook a biophysical and biochemical assessment of stromal-epithelial interactions in noninvasive, invasive and normal adjacent human breast tissue and in breast cancers of increasingly aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
856
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 867 publications
(901 citation statements)
references
References 53 publications
37
856
3
5
Order By: Relevance
“…Interestingly, the lymph node itself is also mechanically active, because Rho inactivation in fibroblastic reticular cells enables lymph node expansion during inflammation (77). Understanding the mechanobiology of T-cell activation is important for immunotherapy design against cancer because the tumor microenvironment is known to undergo significant extracellular matrix remodeling and stiffness changes during disease progression (78). The molecular mechanisms linking cytoskeletal forces with TCR-mediated signaling initiation will be the subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the lymph node itself is also mechanically active, because Rho inactivation in fibroblastic reticular cells enables lymph node expansion during inflammation (77). Understanding the mechanobiology of T-cell activation is important for immunotherapy design against cancer because the tumor microenvironment is known to undergo significant extracellular matrix remodeling and stiffness changes during disease progression (78). The molecular mechanisms linking cytoskeletal forces with TCR-mediated signaling initiation will be the subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been implicated that LOX-mediated collagen cross-linking is critical in ECM stiffness (2,5). Acerbi et al (4) have shown that both ECM stiffness and cellular TGF-β signaling correlated positively with immune cell infiltration in human breast cancer. Leight et al have demonstrated that increased matrix stiffness regulates TGF-β signaling, a potent inducer of EMT in tumor cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been described that inflammation plays an important role in fibrosis as an inducer of epithelial-mesenchymal transition (EMT) in cancer (19). Also, it has been suggested that invasion and aggression of breast cancer correlates with ECM stiffening and immune cell infiltration (4).…”
Section: Association Between Lysyl Oxidase and Fibrotic Focus In Relamentioning
confidence: 99%
See 2 more Smart Citations